Preparation of Ethic codes for studies on laboratory animals - SJ Ale davoud (Babol University of Medical Sciences, 2006)
In most of research programs, uses of laboratory animals are necessary. For this reason we have to prepare comfortable and health situation near their natural life for animals in laboratory. By this manner we try to maintain humanity and omit confounding factors from our research results.We need to gather educational, instrumental and legislation necessity to reach fulfillment of these aims. They could categorize in four fundamental phases.a.Obtain and transport of animalsb.Taking care protocolsc.Knowledge of researchers and workersd.Performance of procedure In each part should be several rules to prepared whole poverty for animals and best situation for research program. A certain code is distinguished for each rule. Researchers have to get permission for each code.They have to get several permission code depend animal species and type of research. Some of these codes such as animal supply have value only for research period but others such as teaching courses may have value for a certain period. Finally use of these codes makes a strait procedure to obtain good results.